Effectiveness of Modified Shoulder Strengthening Therapy on Post-Dislocation Shoulder Function - Danuditya Purna Atmaja; Ainul Ghurri; Japhet Ndayisenga (Universitas Negeri Semarang, 2026)
Shoulder dislocation is one of the joint injuries with a high recurrence rate and has a significant impact on upper extremity function. Limitations in range of motion, decreased muscle strength, and shoulder instability are the main problems following reduction. One rehabilitation approach that has continued to develop is functional movement–based strengthening therapy through Modified Shoulder Flexion and Extension exercises. This study aimed to analyze the effect of this method on pain reduction, improvement in shoulder range of motion, and shoulder muscle strength in patients after shoulder dislocation. The study employed a quasi-experimental design with a pretest–posttest approach involving 18 respondents with anterior shoulder dislocation who met the inclusion criteria and completed the entire intervention program. The intervention was administered for six weeks with a frequency of three sessions per week. Data were analyzed using a paired t-test to compare pre- and post-intervention values for pain (VAS), range of motion, and muscle strength. The results demonstrated a significant reduction in pain, with a mean decrease of 3.8 points on the VAS, along with substantial improvements in shoulder range of motion, particularly in flexion and abduction, which increased by more than 70°. Progressive strengthening of the rotator cuff and deltoid muscles was also observed, with all participants achieving at least a one-grade improvement in Manual Muscle Testing scores.. These findings support the effectiveness of Modified Shoulder Flexion and Extension as an integral component of post–shoulder dislocation physiotherapy rehabilitation.